The Berenstain bears and the in-crowd - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1989)
A rich new cub named Queenie McBear teases Sister Bear and steals her Double-Dutch partners away before the big tournament.
Keywords: Conduct of life -- Fiction; Rope skipping -- Fiction; Bears -- Fiction